Tauroursodeoxycholic acid prevents amyloid-beta peptide-induced neuronal death via a phosphatidylinositol 3-kinase-dependent signaling pathway - Sola, S (2015)
Tauroursodeoxycholic acid (TUDCA), an endogenous bile acid, modulates cell death by interrupting classic pathways of apoptosis. Amyloid-beta (Abeta) peptide has been implicated in the pathogenesis of Alzheimer's disease, where a significant loss of neuron